Rwanda : First Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Rwanda's First Review Under the Policy Support Instrument. Rwanda continues to face the challenge of sustaining high growth while reducing its reliance on aid and preventing the build-up of imbalances. After using foreign exchange reserves over the past few years to support the economy, the room for maneuver is more limited and it will be important to rebuild policy buffers. Growth is projected to increase to 6 percent in 2014. In the short term, the need to support growth and preserve the level of foreign reserves requires a cautious fiscal stance while maintaining priority spending and leaving scope for private sector credit expansion.